The Connection Between The Implementation Of The Right To Health Through The Health Insurance System And State Policy Forms In Mandatory Spending - Fatkhul Muin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Study Purpose: This research focuses on state legal policies regarding efforts to fulfill the right to health through a social security system within the budget. Materials and Methods: This study employed qualitative research with an approach to government policy, including legislation, which serves as the basis for the analysis. Results: State policy regarding the fulfillment of every citizen's constitutional right to health is inseparable from government policy in preparing regional budgets for health. Health spending, as mandatory spending, is clearly stipulated in law and must be met by the government. In the 2026 Financial Note and Draft State Budget, the health budget is set at IDR 244 trillion. This figure represents a 15.8% increase compared to the 2025 outlook of IDR 210.6 trillion. This budget must be a government priority in fulfilling the right to health for every citizen through health insurance. The World Health Organization (WHO) has agreed to achieve Universal Health Coverage (UHC) by 2014. UHC is a health system that ensures that every citizen in the population has equitable access to quality promotive, preventive, curative, and rehabilitative health services at affordable costs. Therefore, the State Budget, which focuses on health, must be able to reduce the burden on society. Conclusion: Mandatory spending in the health sector must be the basis for the government to fulfill the right of every citizen to health insurance and align with Universal Health Coverage (UHC), which is oriented towards the state's strategic role in fulfilling citizens' health rights.